Ácaros associados a palmeiras na Amazônia, com ênfase nos Phytoseiidae (Acari: Mesostigmata) - Cruz, Wilton Pires da [UNESP] (2015)
The mite Raoiella indica Hirst causes significant damage to palm trees in the Carribean area and American continent. Biological control has been considered as a possible means to control this pest. Mites of the family Phytoseiidae (Mesostigmata) are the most extensively predators for biological control of pest mites. Amblyseius largoensis Muma is pointed as a possible control agent of R. indica. Coconut tree is the main host of R. indica, but this pest has also been found on oil palm. The objective of this study was to evaluate the mite fauna on coconut trees and oil palms, in Manaus region, northeastern Amazonas state, analyzing the potential of phytoseiid predators, to determine the occurrence of R. indica and other mites in four distinct periods on coconut trees and to compare the abundance and diversity of the mites of different genotypes of oil palm. A total of 42,225 mites was counted in coconut tree. On the leaflets, 73.9% of the mites were predominantly phytophagous, 6.1% predators and 20.0% of other feeding habits. Eriophyoidea were the predominantly phytophagous mites most abundant on leaflets (57.0%). However, only 4.0% of these were found on fruits. Raoiella indica corresponded to only 1.7 % of the mites found. Phytoseiids were by far the most abundant predators on coconut trees (42.5% of the predators). Amblyseius aerialis (Muma) (254 espécimes), Euseius alatus De Leon (85) and Amblydromalus n. sp. (58) were the most abundant phytoseiids on coconut trees. Cunaxidae corresponded to 64.0% of the phytoseiids. The density of mites in general was only larger in the caiaué (Elaeis oleifera) in the period of intense rainfall. About 91.1% of all mites found on oil palms were phytophagous, predators representing only 3.8%. The species most abundant phytoseiids on the oil palms were Amblyseius perditus Chant & Baker, Iphiseiodes kamahorae De Leon, Amblyseius vasiformis Moraes & Mesa and Iphiseiodes zuluagai Denmark & Muma. In ...